Corrections for mRNA extraction and sample normalization errors find increased mRNA levels may compensate for cancer haplo‐insufficiency. Issue 2 (30th November 2013) - Weaver, David A.; Nestor‐Kalinoski, Andrea L.; Craig, Kristen; Gorris, Matthew; Parikh, Tejal; Mabry, Helen; Allison, David C.
<x xml:space="preserve">Abstract</x> The relative mRNA levels of differentially expressed (DE) and housekeeping (HK) genes of six aneuploid cancer lines with large‐scale genomic changes identified by SNP/SKY analysis were compared with similar genes in diploid cells. The aneuploid cancer lines had heterogeneous genomic landscapes with subdiploid, diploid, and supradiploid regions and higher overall gene copy numbers compared with diploid cells. The mRNA levels of the haploid, diploid, and triploid HK genes were found to be higher after correction of easily identifiable mRNA measurement errors. Surprisingly, diploid and aneuploid HK gene mRNA levels were the same by standard expression array analyses, despite the higher copy numbers of the cancer cell HK genes. This paradoxical result proved to be due to inaccurate inputs of true intra‐cellular mRNAs for analysis. These errors were corrected by analyzing the expression intensities of DE and HK genes in mRNAs extracted from equal cell numbers (50:50) of intact cancer cell and lymphocyte mixtures. Correction for both mRNA extraction/sample normalization errors and total gene copy numbers found the SUIT‐2 and PC‐3 cell lines' cancer genes both had ∼50% higher mRNA levels per single allele than lymphocyte gene alleles. These increased mRNA levels for single transcribed cancer alleles may restore functional mRNA levels to cancer genes rendered haplo‐insufficient by the genetic instability of cancer. © 2013 Wiley Periodicals, Inc.